2011
DOI: 10.1038/ng.857
|View full text |Cite|
|
Sign up to set email alerts
|

CTCF-mediated functional chromatin interactome in pluripotent cells

Abstract: Mammalian genomes are viewed as functional organizations that orchestrate spatial and temporal gene regulation. CTCF, the most characterized insulator-binding protein, has been implicated as a key genome organizer. Yet, little is known about CTCF-associated higher order chromatin structures at a global scale. Here, we applied Chromatin Interaction Analysis by Paired-End-Tag sequencing to elucidate the CTCF-chromatin interactome in pluripotent cells. From this analysis, 1,480 cis and 336 trans interacting loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
610
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 582 publications
(651 citation statements)
references
References 54 publications
36
610
0
5
Order By: Relevance
“…Chromatin interaction analysis with paired-end tag sequencing (ChIA-PET) combines ChIP with a 3C approach and was developed to study genome-wide DNA interactions mediated by a protein of interest [75]. When targeted to CTCF, ChIA-PET uncovered roughly 1500 intra-chromosomal and around 300 interchromosomal interactions mediated by this protein [13]. Subsequent clustering of the regions (10-200 kb) encompassed by the intra-chromosomal loops was done based on the distribution of histone marks.…”
Section: Genome-wide Chromatin Loops Mediated By Ctcfmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin interaction analysis with paired-end tag sequencing (ChIA-PET) combines ChIP with a 3C approach and was developed to study genome-wide DNA interactions mediated by a protein of interest [75]. When targeted to CTCF, ChIA-PET uncovered roughly 1500 intra-chromosomal and around 300 interchromosomal interactions mediated by this protein [13]. Subsequent clustering of the regions (10-200 kb) encompassed by the intra-chromosomal loops was done based on the distribution of histone marks.…”
Section: Genome-wide Chromatin Loops Mediated By Ctcfmentioning
confidence: 99%
“…More than most other transcription factors CTCF appears to bind to intergenic sequences, often at a distance from the transcriptional start site (TSS) [11]. CTCF was one of the first proteins demonstrated to mediate chromatin looping between its binding sites [12,13]. Further evidence for its role in the organization of genome structure comes from observations that it frequently binds to boundaries between chromosomal regions that occupy distinct locations in the nucleus, to boundaries between regions with different epigenetic signatures and/or different transcriptional activities, and to boundaries between recently identified topological domains, which are spatially defined chromosomal units within which sequences preferentially interact with each other [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, NANOG and SOX2 ChIP-seq experiments confirmed that these two pluripotency factors are predominantly enriched in hESCsspecific enhancers but not DFCs-specific enhancers. These results imply that other pluripotency-related factors are preferentially located at hESCs-specific enhancers while developmental factors npg chromatin interactions between enhancers and their corresponding promoters in murine ES cells [7]. How do these predicted cell-specific enhancers regulate gene expression in hESCs?…”
mentioning
confidence: 89%
“…The first two published data sets applying this method interrogated interactions involving the transcription factor estrogen receptor-α [9] in the breast cancer MCF-7 cells and the insulator-binding protein CTCF 10 in mouse embryonic stem cells. However, these proteins are only expected to be involved in a subset of enhancer-promoter interactions in these cells, and thus many enhancerpromoter interactions would be missed in these ChIA-PET data sets.…”
mentioning
confidence: 99%
“…Surprisingly, only 14% of the enhancers had p300 peaks while 23% had peaks for CTCF. There is increasing evidence though for CTCF's role in mediating long-range chromatin interactions [10]. Motif analysis of the enhancers found enrichment for binding sites of a number of regulators of known importance in T-cells.…”
mentioning
confidence: 99%